Analysis of Stress and Deformation Characteristics of Deep-Buried Phyllite Tunnel Structure under Different Cross-Section Forms and Initial Support Parameters - Hao Wu; Xiaohua Yang; Shichun Cai; Binjing Zhao; Kunlong Zheng (Advances in Civil Engineering)
Deep-buried soft rock tunnels exhibit low strength and easy deformation under the influence of high ground stress. The surrounding rock of the soft rock tunnel may undergo large deformation during the construction process, thereby causing engineering problems such as the collapse of the vault, bottom heave, and damage to the supporting structure. The Chengwu Expressway Tunnel II, considered in this study, is a phyllite tunnel, with weak surrounding rock and poor water stability. Under the original design conditions, the supporting structure exhibits stress concentration and large deformation. To address these issues, three schemes involving the use of the double-layer steel arch to support, weakening of the steel arch close to the excavation surface, and weakening of the steel arch away from the excavation surface to support were proposed. Using these schemes, the inverted radius was varied to explore its influence on different support schemes. For simulation, the values of the inverted radius selected were as follows: 1300 cm, 1000 cm, and 700 cm. The proposed support plan was simulated using FLAC3D, and the changes in the pressure between the initial support and surrounding rock, the settling of the vault, and the surrounding convergence were investigated. The numerical simulation results of monitoring the surrounding rock deformation show that the double-layer steel arch can effectively reduce the large deformation of the soft rock well. When the stiffness of one of the steel arches was weakened, the support’s ability to control the deformation was weakened; however, it still showed reliable performance in controlling deformation. However, changing the radius of the invert had an insignificant effect on the deformation and force of the supporting structure.